Integrating Selection Mapping With Genetic Mapping and Functional Genomics - Johnsson, Martin (Frontiers in Genetics, 2018)
Genomic scans for signatures of selection allow us to, in principle, detect variants and genes that underlie recent adaptations. By combining selection mapping with genetic mapping of traits known to be relevant to adaptation, we can simultaneous investigate whether genes and variants show signals of recent selection and whether they impact traits that have likely been selected. There are three ways to integrate selection mapping with genetic mapping or functional genomics: 1. To use genetic mapping data from other populations as a form of genome annotation; 2. o perform experimental evolution or arti cial selection to be able to study selected variants when they segregate, either by performing genetic mapping before selection, or by crossing the selected individuals to some reference population; 3. and to perform a comparative study of related populations facing di erent selection regimes. This short review discusses these di erent ways of integrating selection mapping with genetic mapping and functional genomics, with examples of how each has been done.